A Hospital Based Study on Complications of Childbirth and Associated Risk Factors at Ujjain, Madhya Pradesh - Suchita Singh; Kirti Deshpande; Dharmpal Singh Chouhan; Deepika Badkur (Medsci Publications, 2017)
Objectives: To estimate theprevalence of complications of childbirth among women delivering at district hospital Ujjain and its association with risk factors. Method: An observational follow-up study was conducted among 400 women delivering at district hospital Ujjain MP. Statistical Analysis: Statistical methods applied are: percentage and proportion, mean and standard deviation, chi-square test, multiple logistic regression analysis. Result: The prevalence of complications of childbirth was 59%. The most common complication was hypertension 24.0%, followed by haemorrhage 14.5%, obstructed labour 13.5%, prolonged labour 8.5%.sepsis 7.2%, others 5.3%.Complications of delivery were significantly associated with religion, parity, complaint during ANC visit, and obstetric risk factors. Conclusion: The complications of childbirth were significantly associated with socio-demographic factors (religion and caste), obstetric risk factors, and complaints during ANC visit and parity.